The efficacy of nasal administration of esketamine in patients having moderate-to-severe pain after preoperative CT-guided needle localization: a randomized, double-blind, placebo-controlled trial - Xu, Jiangning; Jian, Jin; Zhang, Yunyun; Wu, Jingxiang; Qiu, Yuwei (Frontiers in Medicine, 2024)
Background: Whether nasal administration of esketamine can provide effective analgesia is unclear in patients with acute pain after preoperative CT-guided needle localization. Methods: In this double-blind, randomized, placebo-controlled trial, patients were assigned to receive either nasal administration of esketamine (0.3mg/kg or 0.5mg/kg) or saline (identical in appearance to esketamine) when they had visual analogue scale (VAS) pain scores > 3/10 during deep breathing after preoperative CT-guided needle localization. The primary outcome was the percentage of patients with satisfactory pain relief, which was defined as VAS pain scores ≤ 3/10 measured 15 min after intranasal of esketamine or saline. Secondary outcomes included VAS measured following esketamine or saline, the incidence and cumulative dose of rescue hydromorphone use, and related adverse events. Results: A total of 90 patients were included in the final analysis. Following intranasal treatment, the percentage of patients with satisfactory pain relief was 83.3% (25/30) in saline group, 43.3% (13/30) in 0.3mg/kg esketamine group and 46.7% (14/30) in 0.5mg/kg esketamine group (p=0.002). The median VAS during deep breathing was less after intranasal administration of esketamine (median [IQR], 3[3, 5] in 0.3 mg/kg or 0.5 mg/kg esketamine compared to saline group (5[4, 6]), p=0.009). The incidence of rescue hydromorphone use was detected less in esketamine group compared to saline group (43.4% in 0.3mg/kg esketamine, 36.7% in 0.5mg/kg esketamine group and 73.3% in saline group, p=0.010). The adverse events were similar among the three groups (p>0.05). Conclusions: Intranasal administration of esketamine is easier and effective to alleviate the acute pain in patients after preoperative CT-guided needle localization without significant adverse effects.